EP341 Screening capacity and cost-effectiveness of the human papillomavirus test versus cervicography as an adjunctive test to Pap cytology to detect high-grade cervical dysplasia. (1st November 2019) - Lee, S-K; Song, T; Seong, SJ
Abstract : Introduction/Background: The purpose of this study was to compare the screening capacities and the cost-effectiveness of cervicography and HPV testing as an adjunctive test to Pap cytology to detect high-grade cervical dysplasia in clinical practice in Korea, a country with a high prevalence of cervical cancer. Methodology: This study was designed by the Korean Cervicography Research Group, established in 1997, and comprises 30 medical university hospital professors who are well trained colposcopists, and who have performed teaching and research activities for cervicography and cervical cancer prevention in Korea. Between January 2015 and December 2016, 33, 531 women underwent a cervicography as a screening test for cervical cancer at private clinics and university hospitals in Korea. SPSS 20.0 (SPSS Inc., Chicago, IL, USA) was used for the statistical analysis. Data were presented as mean standard deviation or median (interquartile range) for quantitative variables and frequency (%) for qualitative variables. Results: In Korea, the cost per patient with CIN2+ is 1474 with the HPV test, and 1135 when cervicography is combined with Pap cytology. Therefore, cervicography co-testing would decrease the cost per patient with CIN2+ lesions by approximately 23% compared to the cost of HPV co-testing. Conclusion: In conclusion, this study suggests that cervicography as an adjunctive test increases detection of cervical cancer and its precursor lesions through reducing false negative errors (2.5% versus 6.3%), compared to the HPV test. Disclosure: Nothing to disclose.